Encoding of movement in near extrapersonal space in primate area VIP - Bremmer, Frank; Schlack, Anja; Kaminiarz, Andre; Hoffmann, Klaus P. (Frontiers in Behavioral Neuroscience, 2013)
Many neurons in the macaque ventral intraparietal area (VIP) are multimodal, i.e., they respond not only to visual but also to tactile, auditory and vestibular stimulation. Anatomical studies have shown distinct projections between area VIP and a region of premotor cortex controlling head movements. A specific function of area VIP could be to guide movements in order to head for and/or to avoid objects in near extra-personal space. This behavioral role would require a consistent representation of visual motion within 3-D space and enhanced activity for nearby motion signals. Accordingly, in our present study we investigated whether neurons in area VIP are sensitive to moving visual stimuli containing depth signals from horizontal disparity. We recorded single unit activity from area VIP of two awake behaving monkeys (M. mulatta) fixating a central target on a projection screen. Sensitivity of neurons to horizontal disparity was assessed by presenting large field moving images (random dot fields) stereoscopically to the two eyes by means of LCD shutter goggles synchronized with the stimulus computer. During an individual trial, stimuli had one of seven different disparity values ranging from 3 degrees uncrossed- (far) to 3 degrees crossed- (near) disparity in 1 degree steps. Stimuli moved at constant speed in all simulated depth planes. Different disparity values were presented across trials in pseudo-randomized order. 61% percent of the motion sensitive cells had a statistically significant selectivity for the horizontal disparity of the stimulus (p<0.05, distribution free ANOVA). 75% of them preferred crossed-disparity values, i.e. moving stimuli in near space, with the highest mean activity for the nearest stimulus. At the population level, preferred direction of visual stimulus motion was not affected by horizontal disparity. Thus, our findings are in agreement with the behavioral role of area VIP in the representation of movement in near extra-personal space.